Right Posterior Approach for Pancreaticoduodenectomy: A New Technical Approach - Okabayashi, Takehiro; Shima, Yasuo; Sumiyoshi, Tatsuaki; Kozuki, Akihito; Tokumaru, Teppei; Saisaka, Yuichi (JOP. Journal of the Pancreas, 2015)
Context The major goals that must be achieved during pancreaticoduodenectomy (PD) include reduction of postoperative hemorrhage and/or operating time. We herein describe a new technique for PD examining right posterior approach PD. Methods From January 2012 to December 2013, 116 patients underwent PD for periampullary or pancreatic disease. Of these 116 patients, 56 cases were surgically treated for pancreas head or periampullary malignancy and were studied for blood loss volume and length of operation. Results An interesting issue in the present study was related to operating time and intra-operative blood loss. The median blood loss volume and operating time were 349 mL (35-3,636 mL) and 276 min (188-467 min), respectively, in patients who underwent a right posterior-approach PD. Conclusion The estimated operative blood loss volume and operative time are lower in right posterior approach PD, probably due to clearly detection a route of the inferior pancreaticoduodenal artery from the SMA and following early ligation of the inferior pancreaticoduodenal artery and reduced congestion of the pancreatic head. Image: Right posterior approach for pancreaticoduodenectomy.